The effect of early prednisolone treatment on the generalization rate in ocular myasthenia gravis. Issue 4 (25th December 2012) - Zach, H.; Cetin, H.; Hilger, E.; Paul, A.; Wuschitz, B.; Jung, R.; Auff, E.; Zimprich, F.
<x xml:space="preserve">Abstract</x> Background and purpose Several small retrospective studies have observed that patients with a purely ocular manifestation of myasthenia gravis (MG) are significantly less likely to convert to a generalized disease when treated early on with corticosteroids. However, given the limited number of reported patients in the literature these findings still remain controversial. Methods In order to increase the number of published cases, we performed a retrospective analysis on 44 patients with newly diagnosed ocular MG who were subsequently either treated with corticosteroids or received no immunosuppressive therapy at all. The generalization rate was assessed at the end of a 2‐year follow‐up period. Results Whereas none of 17 treated patients generalized, 11 of 27 (41%) untreated patients developed generalized symptoms. The difference between the groups was significant (P = 0.003). Conclusions Our results agree well with previous studies on this issue. Taken together, published data indicate risk ratios for generalization of below 0.32 under corticosteroid treatment in comparison to untreated patients.